PENGOLAHAN DAN PENGAMASAN KERIPIK PISANG DAN PISANG COKKO PADA KELOMPOK PKK DESA PARIA KABUPATEN PINRANG - Toto, Herenal Daeng; Marsa, Marsa; Dewi, Ina Yuliana; Nurdiana, Nurdiana (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2022)
Partners in this community service activity are the PKK group in Paria Village, Pinrang Regency. Banana chips and cokko bananas have been produced a lot by the PKK group but unfortunately this business is underdeveloped and seems sober. Very simple packaging design, as well as a lack of knowledge in product promotion. The solutions provided are in the form of socialization of product processing and packaging, assistance in packaging design development, as well as training and provision of tools to package products better. Attractive product packaging design, in an effort to maintain product hygiene.